Antiplatelet activity and TNF-α release inhibition of phthalimide derivatives useful to treat sickle cell anemia - Chelucci, Rafael C. [UNESP]; de Oliveira, Isabela J. [UNESP]; Barbieri, Karina P. [UNESP]; Lopes-Pires, Maria E.; Polesi, Marisa C. [UNESP]; Chiba, Diego E. [UNESP]; Carlos, Iracilda Z. [UNESP]; Marcondes, Sisi; Dos Santos, Jean L. [UNESP]; Chung, ManChin [UNESP] (Springer Nature, 2019)
Sickle Cell Anemia (SCA) is one of the most prevalent hereditary hematological diseases worldwide. The disease is characterized by chronic inflammation, hypercoagulable state, and pro-thrombotic profile, which lead the vaso-occlusive process. In this work, we described the antiplatelet activity and the ability to reduce tumor necrosis factor-alpha (TNF-α) levels of phthalimide derivatives. All compounds inhibited platelet aggregation induced by collagen and adenosine diphosphate, at levels ranging from 26.0 to 74.2% and 30.7 to 79.6%, respectively. The compounds exhibited reduced bleeding time compared to acetylsalicylic acid (ASA). Moreover, compounds 4c and 10c inhibited TNF-α levels at 73.5% and 65.0%, respectively. These findings suggest that phthalimide derivatives 4c and 10c are promising lead compounds useful to prevent vaso-occlusion and inflammation associated with the sickle cell anemia.
Keywords: Phthalimide; Platelet aggregation inhibition; Sickle cell disease; TNF-α inhibition; Vaso-occlusion